Porphyrin-based framework materials for energy conversion - Jiawei Gu; Yi Peng; Ting Zhou; Jiao Ma; Huan Pang; Yusuke Yamauchi (Nano Research Energy, 2022)
With the increasing demand for fuel causing serious environmental pollution, it is urgent to develop new and environmentally friendly energy conversion devices. These energy conversion devices, however, require good, inexpensive materials for electrodes and so on. The multifunctional properties of porphyrins enable framework materials (e.g., metal-organic frameworks and covalent organic frameworks) to be applied in energy conversion devices due to their simple synthesis, high chemical stability, abundant metallic active sites, adjustable crystalline structure and high specific surface area. Herein, the types of porphyrin structural blocks are briefly reviewed. They can be used as organic ligands or directly assembled with framework materials to generate high-performance electro-/photo-catalysts. These types of catalysts applied in electro-/photo-catalytic water splitting, electro-/photo-catalytic carbon dioxide reduction, and electrocatalytic oxygen reduction are also summarized and introduced. At the end of the article, we present the challenges of porphyrin-based framework materials in the above application and corresponding solutions. We expect porphyrin-based framework materials to flourish energy conversion in the coming years.